Effects of Ni content on the shape memory properties and microstructure of Ni-rich NiTi-20Hf alloys. (9th August 2016) - Saghaian, S M; Karaca, H E; Tobe, H; Pons, J; Santamarta, R; Chumlyakov, Y I; Noebe, R D
Abstract: Shape memory properties and microstructure of four Ni-rich NiTiHf alloys (Ni50.3 Ti29.7 Hf20, Ni50.7 Ti29.3 Hf20, Ni51.2 Ti28.8 Hf20, and Ni52 Ti28 Hf20 (at.%)) were systematically characterized in the furnace cooled condition. H-phase precipitates were formed during furnace cooling in compositions with greater than 50.3Ni and the driving force for nucleation increased with Ni content. Alloy strength increased while recoverable strain decreased with increasing Ni content due to changes in precipitate characteristics. When the precipitates were small (∼5–15 nm), they were readily absorbed by martensite plates, which resulted in maximum recoverable strain of 2% in Ni50.7 Ti29.3 Hf20 . With increasing Ni content, the size (>100 nm) and volume fraction of precipitates increased and the growth of martensite plates was constrained between the precipitates when the Ni concentration was greater than 50.7 at.%. Near perfect dimensional stability with negligible irrecoverable strain was observed at stress levels as high as 2 GPa in the Ni52 Ti28 Hf20 alloy, though the recoverable strain was rather small. In general, strong local stress fields were created at precipitate/matrix interphases, which lead to high stored elastic energy during the martensitic transformation.